Simulated nutrient dissolution of Asian aerosols in various atmospheric waters: Potential links to marine primary productivity. (September 2017) - Wang, Lingyan; Bi, Yanfeng; Zhang, Guosen; Liu, Sumei; Zhang, Jing; Xu, Zhaomeng; Ren, Jingling; Zhang, Guiling
Abstract: To probe the bioavailability and environmental mobility of aerosol nutrient elements (N, P, Si) in atmospheric water (rainwater, cloud and fog droplets), ten total suspended particulate (TSP) samples were collected at Fulong Mountain, Qingdao from prevailing air mass trajectory sources during four seasons. Then, a high time-resolution leaching experiment with simulated non-acidic atmospheric water (non-AAW, Milli-Q water, pH 5.5) and subsequently acidic atmospheric water (AAW, hydrochloric acid solution, pH 2) was performed. We found that regardless of the season or source, a monotonous decreasing pattern was observed in the dissolution of N, P and Si compounds in aerosols reacted with non-AAW, and the accumulated dissolved curves of P and Si fit a first-order kinetic model. No additional NO3 −  + NO2 − dissolved out, while a small amount of NH4 + in Asian dust (AD) samples was released in AAW. The similar dissolution behaviour of P and Si from non-AAW to AAW can be explained by the Transition State Theory. The sources of aerosols related to various minerals were the natural reasons that affected the amounts of bioavailable phosphorus and silicon in aerosols (i.e., solubility), which can be explained by the dissolution rate constant of P and Si in non-AAW with lower values in mineral aerosols. The acid/particle ratio and particle/liquid ratio also have a large effect on the solubility of P and Si, which was implied by Pearson correlation analysis. Acid processing of aerosols may have great significance for marine areas with limited P and Si and post-acidification release increases of 1.1–10-fold for phosphorus and 1.2–29-fold for silicon. The decreasing mole ratio of P and Si in AAW indicates the possibility of shifting from a Si-limit to a P-limit in aerosols in the ocean, which promotes the growth of diatoms prior to other algal species. Highlights: Acid processing promotes the release of NH4 + in Asian dust. P and Si in aerosols have similar dissolution pattern but different solubility. P and Si dissolution of Asian aerosols in AW fit first-order kinetic model. Source, acid/particle ratio and Pc co-control the P and Si solubility in aerosols. Dissolved P and Si of Asian aerosols in AAW far exceed that in non-AAW.